Simulasi Keruntuhan Bendungan Jatibarang Kota Semarang menggunakan Program HEC – RAS 2D - Wardana, Yoszy Kusuma; Aziz, S. Kamilia; Rahman Alam, Rizki Robbi; Indriyani, Dwi (Jurnal Aplikasi Teknik Sipil, 2024)
The collapse of the dam has a significant impact on the downstream area of the dam. These impacts can be minimized by conducting a dam collapse simulation. There are two main causes of dam collapse, namely overtopping and piping. From the hydrological analysis of the Jatibarang Dam, it is determined that overtopping is not a concern. Therefore, the dam collapse analysis utilizes the piping analysis method. Dam collapse modeling is carried out using the HEC-RAS 2D program with the Froehlich 2008 regression method, as the dam is of the embankment type. According to the simulation results, a dam collapse at the Jatibarang Dam would result in a flood affecting an area of 30.590 km2 downstream of the dam.